Photobioreactors for building integration: A overview of designs and architectural potential - Arora, Ruma; Sudhakar, Kumarasamy; Rana, R. S. (Elsevier Ltd, 2024)
The global community faces critical energy and environmental challenges, necessitating innovative solutions to ensure a sustainable future.In response to these challenges, this paper explores the potential of integrating microalgal biotechnology with renewable energy systems within buildings. This innovative approach could transform architecture into a "bio-factory" capable of producing food, energy, and other valuable products.The success of this concept hinges on developing highly efficient photobioreactors specifically designed for building integration. Optimizing these systems requires careful consideration of design parameters, growth rate models, and factors influencing performance within diverse urban environments.Furthermore, integrating these systems must prioritize productivity and aesthetics to promote urban self-sufficiency and a sustainable built environment. By utilizing microalgae and renewable energy sources, building-integrated photobioreactors offer a promising solution for reducing energy consumption and carbon footprints in modern buildings.